Expression of NADPH oxidase (NOX) 5 in rabbit corneal stromal cells. - Farhan Rizvi (PLoS ONE, 2012)
To determine whether NOX 5 is expressed in rabbit corneal stromal cells (RCSC). NADPH oxidases (NOXes) are enzymes that preferentially use NADPH as a substrate and generate superoxide. Several isoforms of NOXes function as multi-protein complexes while NOX5 and DUOXs do not require the accessory proteins for their activity and possess calcium binding EF hands.Human NOX5 primers were used to amplify the rabbit NOX5 by RT-PCR. Amplified product was sequenced to confirm its identity. The protein encoded by the NOX5 was identified by western blot analysis. NOX5 siRNA was used to reduce transcript, protein, and calcium stimulated activity. In silico analyses were performed to establish the putative structure, functions, and evolution of rabbit NOX5.NOX activity was measured in RCSC with NADPH rather than NADH as a substrate. RT-PCR with NOX5 primers amplified 288 bp product using RCSC cDNA, which, when sequenced, confirmed its identity to human NOX5 mRNA. This sequence was used to predict the rabbit (Oryctolagus cuniculus) NOX5 gene. NOX5 siRNA reduced amounts of NOX5 mRNA in RCSC and reduced ionomycin stimulated superoxide production. A protein of about 65 to 70 kDa encoded by the NOX5 was detected by western blot analysis. In silico analysis predicted a putative rabbit NOX5 protein containing 801 amino acids. Motif searches predicted the presence of at least 3 putative EF-hands in N-terminus and a NOX domain in C terminal region.The data document that the NOX5 gene was expressed in cells of lagomorphs unlike rodents, making the rabbit an interesting model to study NOX5 functions. The activity of the rabbit NOX5 was calcium stimulated, a trait of NOX5 in general. NOX5 may also prove to be a useful genetic marker for studying the taxonomic position of lagomorphs and the Glires classification.